2017
DOI: 10.1039/c6ta06961d
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature densification of Al-doped Li7La3Zr2O12: a reliable and controllable synthesis of fast-ion conducting garnets

Abstract: A hybrid sol–gel solid-state procedure employing 3 h calcination at 1100 °C is used to produce fast-ion conducting Al-doped Li7La3Zr2O12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 32 publications
6
80
0
Order By: Relevance
“…Indeed, Rettenwander et al indicated that while Ga-rich LLZO displayed denser microstructures with better connected grains and smaller pores,Al-rich LLZO lead simultaneously to more pronounced separation of grains and increased grain sizes. The difficulty of producing dense Al-substituted garnets has been previously reported, and new synthesis methods have been developed to overcome this problem 17,65,66.…”
mentioning
confidence: 99%
“…Indeed, Rettenwander et al indicated that while Ga-rich LLZO displayed denser microstructures with better connected grains and smaller pores,Al-rich LLZO lead simultaneously to more pronounced separation of grains and increased grain sizes. The difficulty of producing dense Al-substituted garnets has been previously reported, and new synthesis methods have been developed to overcome this problem 17,65,66.…”
mentioning
confidence: 99%
“…The highly conductive cubic phase have reported that Al dopants play a key role as cubic-phase stabilizers by replacing lithium lattice sites (e.g. 24d, 48 g, and 96 h) [10,11,14,18,23,25] . Although the exact Al sites replacing Li sites are not experimentally clear, it seems quite certain that Al substitution could produce a stabilized cubic phase and provide fast Li-ion conduction.…”
Section: Resultsmentioning
confidence: 99%
“…Tetragonal phase peaks were also observed at approximately 57 °and 59 °in the XRD pattern of the Li 7-y La 3 Zr 2 O 12 , indicating that the cubic phase became unstable owing to the loss of Li during the sintering process at 10 0 0 °C [11] . However Al-LLZO retained a solid cubic phase except for the formation of La 2 Zr 2 O 7 [26] , since Shinawi et al reported that several secondary phases can act as cubic-phase stabilizers to improve Li-ion conductivity [23] . With the same point of view, Al incorporation might have influenced the structural formation of secondary phases in the samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of energy‐utilizing converter cells, all‐solid‐state lithium‐ion batteries have been gradually replaced the traditional liquid lithium‐ion batteries because the application of solid electrolyte avoids the disadvantage of expansion or even explosion problems caused by liquid batteries . Solid electrolytes play a vital role in all‐solid‐state lithium‐ion batteries due to the electron‐blocking and ion‐conducting effects between the cathode and anode electrodes…”
Section: Introductionmentioning
confidence: 99%